2019
DOI: 10.1093/jncics/pkz068
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Validation of the CamGFR Model for Estimated Glomerular Filtration Rate

Abstract: Important oncological management decisions rely on kidney function assessed by serum creatinine–based estimated glomerular filtration rate (eGFR). However, no large-scale multicenter comparisons of methods to determine eGFR in patients with cancer are available. To compare the performance of formulas for eGFR based on routine clinical parameters and serum creatinine not calibrated with isotope dilution mass spectrometry, we studied 3620 patients with cancer and 166 without cancer who had their glomerular filtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…21 It remains commonly used for the prescription of cancer chemotherapy, despite increasing evidence of its limitations (Supplementary Table S19). [7][8][9]22 Updated draft guidance from regulatory agencies in 2020 recommends eGFR using the MDRD or CKD-EPI equations for pharmacokinetic studies for drug development programs. 23 Our data on equation performance, along with these updated guidelines, should encourage the oncology community to incorporate newer equations that enable more accurate GFR estimation into clinical practice and research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 It remains commonly used for the prescription of cancer chemotherapy, despite increasing evidence of its limitations (Supplementary Table S19). [7][8][9]22 Updated draft guidance from regulatory agencies in 2020 recommends eGFR using the MDRD or CKD-EPI equations for pharmacokinetic studies for drug development programs. 23 Our data on equation performance, along with these updated guidelines, should encourage the oncology community to incorporate newer equations that enable more accurate GFR estimation into clinical practice and research.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in patients with solid tumors have shown a potential for error in chemotherapy prescriptions using the CG equation. [7][8][9] Estimated GFR (eGFR) based on Scr (eGFRcr) using the CKD-EPI equation is recommended as the "first test" for GFR evaluation for routine clinical practice in adults. 10 Patients with cancer were not well represented in the studies in which newer eGFR equations were derived, and for several reasons, the CKD-EPI equation may be less accurate in patients with cancer than in the general population.…”
mentioning
confidence: 99%
“…1) [1]. However, the optimal strategy for measurement of the glomerular filtration rate (GFR) and thus for dosing carboplatin is the subject of much debate [2][3][4][5]. GFR is most accurately measured (mGFR) using isotopic methods such as 51Cr-EDTA [6], but such assays are often impractical.…”
Section: Introductionmentioning
confidence: 99%
“…GFR is most accurately measured (mGFR) using isotopic methods such as 51Cr-EDTA [6], but such assays are often impractical. Multiple formulae to estimate GFR (eGFR) have been developed, predominantly in non-cancer patient populations [3,[7][8][9][10]. These formulae frequently result in significant measurement error, compared with isotopic mGFR, particularly at the extremes of body weight [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation